Analisis Penerapan Sistem Keuangan Desa (Siskeudes) dalam Pengelolaan Keuangan Desa di Kecamatan Kota Soe Kabupaten Timor Tengah Selatan - Regina Rambu Lika Rawambaku; Anthon Simon Y. Kerihi; Siprianus G. Tefa (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to analyze the implementation of the Village Financial System (Siskeudes) in the management of village finances in Kota SoE Subdistrict, South Central Timor Regency. The implementation of Siskeudes is expected to enhance transoarency, accountability, and effeciency in village financial management. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The result of the study indicate that the implementation of Siskeudes in Kota SoE Subdistrict has been running well, although there are still some obstacles such as the lack of understanding among village officials about the system and limited supporting infastructure. Nevertheles, Siskeudes has had a positive impact on village financial management, such as improving the quality of financial reporting and supervision. This study recommends increasing training and socialization for village officials and improving infrastructurue to support the optimal implementation of Siskeudes in the future.